Rethinking performance crises in professional soccer: German coaches’ insights into systemic vulnerabilities and escalating dynamics - Constantin Rausch; Julian Fritsch; Stefan Altmann; Jan Spielmann; Lena Steindorf; Darko Jekauc (PLoS ONE, 2026)
Professional soccer, as a global phenomenon, is characterized not only by outstanding performances but also by frequent and sometimes prolonged periods of underperformance, which represent performance crises. Despite the growing body of research on performance crisis, the specific perspectives of coaches remain underexplored. Previous studies have largely focused on players’ viewpoints, resulting in a lack of understanding of the systemic and escalating dynamics of crises from the perspective of those in leadership positions. This study addresses this gap by investigating how professional soccer coaches perceive the development and persistence of performance crises in professional soccer. Employing a qualitative research design, twelve professional coaches with diverse roles (head coaches, assistant coaches, and goalkeeper coaches), a mean age of 43 years (range: 32–51), and extensive coaching experience in professional soccer (7–23 years, M = 15.5) were interviewed. The interviews were analyzed using data-driven and concept-driven content analysis based on thematic qualitative text analysis. The analysis reveals that performance crises are not attributable to isolated incidents but rather arise from the interplay between pre-crisis vulnerabilities, their transition to crisis dynamics, acute triggers, and escalating dynamics at team, organizational, and external levels. Pre-crisis vulnerabilities include latent factors such as organizational incongruence, and fragile team cohesion, that increase susceptibility to crises. Notably, coaches emphasized that success temporarily masks these underlying tensions, which surface and intensify when performance declines. Acute triggers refer to specific disruptive events or negative results that catalyze instability and initiate the crisis process. Escalating dynamics describe the self-reinforcing processes whereby psychological, social, and structural problems perpetuate and deepen the crisis. The study advances the field by highlighting systemic, self-reinforcing cycles of crisis and organizational incongruence that undermine coaching authority. These insights have practical implications for improving leadership coherence and resilience strategies in professional sports environments.